MODEL PENDEKATAN ALAT UJI KEPADATAN RINGAN UNTUK TANAH DI LABORATORIUM (PENELITIAN LANJUTAN I) - Anwar Muda (Anterior Jurnal, 2017)
The study, entitled "the application of the Model as a means of Testing the density of light to the ground in the lab (Advanced Studies 1)". Backed by research from previous research, entitled "the application of the Model as a means of Testing the density of light for the soil in the laboratory", in previous studies of soil clays used example is the land of clays from the village of Baringan, the city of Palangkaraya. While soil samples in this study used is the land of the village of Palopat Sub-district of Padang Sidempuan PK, Southeast, or rather in the STA 500 Padang Sidempuan 4 heading Mandailing Natal. This study aimed to compare the CBR and UCS clay stabilized sand and cement for the pavement. The research aims to conduct an analysis of the maximum density of soil clays based on Models by as much as 33 collisions per layer as much as 2 layers obtained the maximum dry weight (γd max) and optimum moisture content (w opt) and SNI 1742:2008. If the level of the margin of error is obtained and has 5% < assessment of performance against the same heap, then the Model can be used as a means of testing the density of light to the ground in a lab that has the same standard with SNI 1742:2008.